2005
DOI: 10.1111/j.1365-2567.2004.02079.x
|View full text |Cite
|
Sign up to set email alerts
|

Tick saliva inhibits differentiation, maturation and function of murine bone‐marrow‐derived dendritic cells

Abstract: SummaryHaematophagous arthropod vectors such as mosquitoes, tsetse flies, sandflies and ticks have evolved salivary immunomodulatory factors that prevent the vertebrate host from rejecting them meanwhile enhancing pathogen transmission. As dendritic cells (DC) play a major role in host immune responses, we studied the effects of Rhipicephalus sanguineus tick saliva on DC differentiation and maturation. Flow cytometry analysis revealed that the addition of saliva to bone marrow cells inhibits the differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
69
3
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 62 publications
(134 reference statements)
8
69
3
4
Order By: Relevance
“…Tick saliva also modulates cytokine production by epidermal cells (35) and alters expression of adhesion molecules by skin-derived endothelial cells (36). More recently, a study demonstrated that saliva from R. sanguineus inhibits differentiation, maturation, and cytokine synthesis of bone marrow-derived DCs (20). Despite the critical role of immunomodulators in tick-host interaction, the molecular cloning and identification of most of these molecules have not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tick saliva also modulates cytokine production by epidermal cells (35) and alters expression of adhesion molecules by skin-derived endothelial cells (36). More recently, a study demonstrated that saliva from R. sanguineus inhibits differentiation, maturation, and cytokine synthesis of bone marrow-derived DCs (20). Despite the critical role of immunomodulators in tick-host interaction, the molecular cloning and identification of most of these molecules have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, splenocytes from C3H/ HeJ mice infested with I. scapularis nymphs presented decreased production of IL-2 and IFN-␥ and increased production of IL-4 and IL-10 when stimulated with Con A (17,18). Also, saliva of Rhipicephalus sanguineus inhibited Con A-induced IL-2 production by splenocytes (19) and IL-12 production by LPS-stimulated bone marrow-derived DCs (20). Despite the potentially critical role of these molecules in the biology of tick feeding and host-vector interaction, their molecular identification has remained elusive to date.…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…The tick saliva has been reported to inhibit differentiation and LPS induced-maturation of bone marrow-derived DCs (BMDCs) in vitro (15). More recently, prostaglandin E 2 contained in the tick saliva has been found to impair cytokine production by BMDCs as well as their capacity to induce T cell proliferation (16).…”
Section: Discussionmentioning
confidence: 99%
“…Cavassani et al (15) described an inhibitory effect on DC differentiation and LPS induced maturation. More recently, it has been shown that prostaglandin E 2 present in tick saliva inhibits IL-12 and TNF-␣ production by DCs (16).…”
mentioning
confidence: 99%
“…It has already been shown that they use Salp15 to inhibit the activation and proliferation of CD4 ϩ T cells by binding to its CD4 receptor (1,6,13). In addition, tick salivary proteins have been found to inhibit B cells (8), dendritic cells (4,11), NK cells (17), neutrophils (20), and macrophages (7). Isac (5,27) and Salp20 (26) are two salivary proteins that were shown to inhibit the alternative pathway of the complement system.…”
Section: Discussionmentioning
confidence: 99%